Nursing Students' Perception of Clinical Teaching and Learning in Ghana: A Descriptive Qualitative Study - Sarah Ama Amoo; Yaa Boahemaa Gyasi Aderoju; Richard Sarfo-Walters; Patience Fakornam Doe; Christiana Okantey; Christian Makafui Boso; Susanna Aba Abraham; Andrews Adjei Druye; Nancy Innocentia Ebu Enyan (Hindawi Limited, 2022)
Background. Clinical teaching and learning are critical in bridging the theory-practice gap in nursing education. This study aimed at exploring nursing students' perception of clinical teaching and learning in Ghana. In particular, this study sought to (1) describe the factors that promote clinical teaching, (2) examine students' perception of clinical teaching, (3) describe the impact of clinical learning on students, and (4) explore ways of improving clinical teaching and learning. Methods. A descriptive qualitative study was conducted with 16 final-year nursing students using telephone-based interviews. Individual in-depth interviews were conducted with a semistructured interview guide, and data were analysed by the qualitative thematic analysis. Results. The findings indicate that being taught new things, being supervised, and having autonomy were the most significant factors that promoted clinical learning. Participants also reported that clinical experience created learning opportunities that helped develop clinical competence. They described learning experiences in the clinical setting as good, albeit gaps in practice. Poor staff attitude, lack of equipment, poor student attitude, inadequate learning opportunities, and lack of clinical supervisors were perceived as challenges in the clinical environment. Conclusions. Efforts to consciously teach, supervise, and challenge students to have independence in the clinical area will promote clinical teaching and learning. Therefore, nursing educational institutions and all other stakeholders need to collaborate in eliminating the numerous challenges students encounter in the clinical environment.